Valorization of palm oil empty fruit bunch biomass into sulfonated lignin nanoparticles as sustainable retarders for high-temperature oilwell cement systems - Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Nwaichi, Eucharia Oluchi; Umunnawuike, Chika; Abutu, David; Nyah, Francis; Ngouangna, Eugene N.; Agi, Augustine Aja (Springer Nature, 2026)
The growing need for sustainable materials in the energy and infrastructure sectors has intensified efforts to valorize lignocellulosic biomass into high-value functional additives. This study addresses the limited availability of eco-efficient cement retarders capable of performing under ultra-high-temperature (UHT) oilwell conditions by developing sulfonated lignin nanoparticles (SLNP) derived from empty fruit bunch (EFB) biomass. Lignin was extracted via dual-step acid–alkali hydrolysis and subsequently sulfonated using sodium bisulfite to introduce hydrophilic sulfonate (–SO₃⁻) groups. The synthesized SLNPs were characterized using Field emission scanning electron microscopy (FESEM). Fourier transform infrared spectroscopy (FTIR), gas chromatography-mass spectroscopy (GC-MS), and thermal analyses to evaluate morphology, chemical functionality, and intrinsic thermal behavior. FESEM revealed uniform spherical nanoparticles (16–33 nm), while FTIR and GC–MS confirmed successful sulfonation and the presence of oxygenated aromatic functionalities. Thermal analysis indicated improved structural stability, with SLNP retaining approximately 30% residual mass at 1000 °C compared to 25% for unmodified lignin nanoparticles (LNP). In cement slurry evaluation, SLNP demonstrated tunable and consistent retardation, extending setting time by up to 40% relative to neat cement at 250 °C, with performance comparable to sodium gluconate at a lower dosage. The retarding action is attributed to adsorption and electrostatic interactions between sulfonated functional groups and reactive clinker phases (C₃S and C₃A), which delay hydration while maintaining dispersion stability. Overall, EFB-derived SLNP exhibit promising performance under elevated laboratory temperatures, highlighting their potential as a bio-based, thermally resilient retarder and contributing to biomass valorization and circular material development.